2015
DOI: 10.5935/1678-9741.20150073
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mortality After CABG Surgery

Abstract: INTRODUCTIONNumerous studies have shown that women undergoing coronary artery bypass graft surgery present higher mortality rate during hospitalization, and often complications when compared to men.OBJECTIVETo compare the mortality of men and women undergoing coronary artery bypass graft surgery and identify factors related to differences occasionally found.METHODSRetrospective cohort study conducted with 215 consecutive patients who underwent coronary bypass surgery.RESULTSWomen had a higher average age. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…There is also inconsistency between gender difference and postoperative outcomes following CABG in the previous studies when examined and compared with each other. In many studies female gender was found associated with worse postoperative outcomes after CABG surgery [ 8 - 11 ] , while in some other studies which especially had the propensity-matching for the adjustment of risk factors, demonstrated that the outcomes in females were similar to their matched male counterpart following CABG [ 12 - 15 ] . Thus, the impact of gender difference on postoperative outcomes after CABG is a debated topic of ongoing relevance.…”
Section: Introductionmentioning
confidence: 99%
“…There is also inconsistency between gender difference and postoperative outcomes following CABG in the previous studies when examined and compared with each other. In many studies female gender was found associated with worse postoperative outcomes after CABG surgery [ 8 - 11 ] , while in some other studies which especially had the propensity-matching for the adjustment of risk factors, demonstrated that the outcomes in females were similar to their matched male counterpart following CABG [ 12 - 15 ] . Thus, the impact of gender difference on postoperative outcomes after CABG is a debated topic of ongoing relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on gender differences after OPCAB surgery are scarce [ 16 , 17 , 18 , 19 , 20 ]. Previous retrospective trials have shown that female gender might be an independent risk factor for operative mortality [ 14 , 23 ]. Similarly, Alam et al [ 24 ] found increased operative and 30-day mortality rates in females compared to males after bypass surgery.…”
Section: Discussionmentioning
confidence: 99%